2020
DOI: 10.1111/jog.14192
|View full text |Cite
|
Sign up to set email alerts
|

Association of vascular endothelial growth factor A polymorphisms and aberrant expression of connexin 43 and VEGFA with idiopathic recurrent spontaneous miscarriage

Abstract: Aim Idiopathic recurrent spontaneous miscarriage (IRSM) is one of the pregnancy outcomes that affects 1–2% of women trying to conceive. Specific genotype or aberrant expression of vascular endothelial growth factor A (VEGFA) and connexin 43 (Cx43) as two important genes for embryonic development are deemed to increase the risk of IRSM. Methods To investigate any possible association of VEGFA polymorphisms and aberrant expression of Cx43 and VEGFA with IRSM, we carried out a case–control study including embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…There are seven studies that investigated the polymorphisms rs2010963 and rs833061 of the VEGF gene. Three studies did not confirm any association between PCOS and the polymorphisms investigated 17 , 19 , 20 , a result similar to that found in this study. In contrast, other studies found an association of polymorphism rs2010963 17 , 22 , 23 and rs833061 10 with PCOS.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…There are seven studies that investigated the polymorphisms rs2010963 and rs833061 of the VEGF gene. Three studies did not confirm any association between PCOS and the polymorphisms investigated 17 , 19 , 20 , a result similar to that found in this study. In contrast, other studies found an association of polymorphism rs2010963 17 , 22 , 23 and rs833061 10 with PCOS.…”
Section: Discussionsupporting
confidence: 69%
“…Several VEGF SNPs are associated with various conditions in women, including endometriosis 17 , 18 , recurrent miscarriage 19 , and preeclampsia 20 . These results together suggest that VEGF SNP can contribute to the pathogenesis of female reproductive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In VEGF 634 G > C, the allele C and CC genotype are significantly more frequent in individuals with RPL than in the control group ( p < 0.0001) [ 43 ]. Thus, the frequency of idiopathic RSA can be dependent on the GC and CC genotype of rs2010963 VEGF polymorphism [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential role of HIF1A in the development of prematurity-related diseases has yet to be investigated. On the other hand, previous studies have suggested that VEGFA variants may be associated with female reproductive diseases [28][29][30], and some neonatal populations have shown potential links between VEGFA and the consequences of prematurity, although these have not been consistently replicated [31]. Thus, the main objective of our analysis is to comprehensively examine the associations between HIF1A SNPs (rs11549465 and rs11549467) and VEGFA SNPs (rs2010963 and rs833061) with the occurrence of NEC, BPD, IVH, RDS, DWMI, or ROP, taking into account the presence of hypoxia at birth.…”
Section: Introductionmentioning
confidence: 95%